Measurement of Diameter and Scale of Cashmere Fibers by Computer Images Analysis (Journal of Fiber Bioengineering and Informatics, 2012)
This paper mainly studies computer automatic measurement of cashmere diameter and area of cashmerefiber scales. It firstly uses Matlab7.0 to do simulation experiments to determine the appropriate imageprocessing program that is suitable for fiber images obtained under optical microscope. The workflow ofimage processing includes image format conversion, image denoising, image segmentation, binarization,extraction of fiber edge and modificatory process. After image processing, it obtains the necessary binaryimage needed by the automatic measurement of parameters. The binary image is the basis of diameterand scale-area measurement of cashmere. This paper designs sub-measurement algorithm to achievethe automatic measurement of fiber diameter and pixel-measurement through pixel-by-point scanningto achieve the automatic measurement of area of cashmere fiber scales. It eliminates the error causedby the influence of man-made factors and improves the accuracy of the measurement, which lays thefoundation of automatic identification.